E-Worksheets Based on STEAM-PJBL with Local Coastal Wisdom to Improve Critical Thinking Skills - Winarni, Endang Widi; Heryanto, Debi; Yusnia, Yusnia; Agusdianita, Neza; Purwandari, Endina Putri; Wijanarko, Andang (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This research aimed to investigate the influence of electronic student worksheets based on STEAM and Project-Based Learning (PjBL) with local coastal wisdom content to improve the critical thinking abilities of fifth-grade students in Group V elementary schools in Bengkulu City. This research employed a quantitative approach using a quasi-experimental method with a Matching Only Pretest-Posttest Control Group Design. The population of this study comprised all elementary schools in Group V, Bengkulu City. The sample consisted of fifth-grade students from SDN 09 and 02 Bengkulu City, selected using Cluster Random Sampling. The research instrument used was a critical thinking skills test with a pretest and posttest. The data was analysed quantitatively using descriptive statistics, prerequisite tests, and hypothesis testing. The t-test was used to test the hypothesis. The results showed that the significance value (2-tailed) was 0.000 < 0.05 at a 5% significance level. The average scores of the experimental class (80.28) and the control class (50.21) showed a significant difference between the learning outcomes of the experimental and control classes. It can be concluded that the experimental class using electronic student worksheets based on STEAM and PjBL significantly influenced the students' critical thinking abilities. In conclusion, this study found a significant influence of electronic student worksheets based on STEAM and PjBL on the critical thinking skills of fifth-grade students in Group V elementary schools in Bengkulu City.